2010
DOI: 10.4103/0019-5545.69255
|View full text |Cite
|
Sign up to set email alerts
|

Indian research on suicide

Abstract: The suicide rate in India is 10.3. In the last three decades, the suicide rate has increased by 43% but the male female ratio has been stable at 1.4 : 1. Majority (71%) of suicide in India are by persons below the age of 44 years which imposes a huge social, emotional and economic burden. Fifty four articles on suicides have been published in IJP. Several studies reveal that suicidal behaviours are much more prevalent than what is officially reported. Poisoning, hanging and self immolation (particularly women)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 12 publications
7
68
0
1
Order By: Relevance
“…9,10 Suicidal tendencies and depression are giving way to the newer phenomena of Injuries and violence. 11 It is indeed a worrisome situation.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Suicidal tendencies and depression are giving way to the newer phenomena of Injuries and violence. 11 It is indeed a worrisome situation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, every 40 seconds, a person commits suicide being the second leading cause of death among 15-29 year old 1,2 . High suicidality rates are a widespread concern, particularly in Western 3 and Central Europe 4 , the U.S. 5 , Asiatic countries such as Russia and former Socialist Republics 6 , South Korea 6 , China 7 , India 8 , Sri Lanka 9 ; and Latin American countries such as Cuba 10 , Uruguay 11 ; Ecuador 12 , Bolivia 13 , Brazil 14 , Argentina 15 and Colombia 16 . Suicide risk increases in people with mental disorders or impulsive behavior, those facing stressful situations or with easy access to harmful tools such as poisoning, hanging and firearms 17 .…”
Section: Introductionmentioning
confidence: 99%
“…[1,9] Even studies carried out in India reported similar finding. [5,10] One of the main reason behind this is nature of suicide attempt that was irreversible type of attempt were different for both genders. Females were involved in less violent nature of suicide attempts than males and hence deaths were avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The incidence rate of suicide among adolescents is increasing in India also. [5] For adolescent between the ages of 10 and 24, suicide is the third leading cause of death, significantly superseding the rate for adults aged 35 to 54 years. [6] Males are more likely to die as a result of suicide, whereas in almost all regions of the world, nonlethal suicide attempts are more common in females.…”
Section: Introductionmentioning
confidence: 99%